Neural Predictive Control of Unknown Chaotic Systems - Boukabou, A.; Mansouri, N. (Nonlinear Analysis: Modelling and Control, 2005)
In this work, a neural networks is developed for modelling and controlling a chaotic system based on measured input-output data pairs. In the chaos modelling phase, a neural network is trained on the unknown system. Then, a predictive control mechanism has been implemented with the neural networks to reach the close neighborhood of the chosen unstable fixed point embedded in the chaotic systems. Effectiveness of the proposed method for both modelling and prediction-based control on the chaotic logistic equation and Hénon map has been demonstrated.
Keywords: chaos; neural networks; predictive control